Técnicas para disminuir la monilla (Moniliophthora roreri) en el cultivo de cacao (Theobroma cacao L) - Castro León, Angy Betzaida (2025)
This case study, since it is a disease that affects the quantity and quality of the pod, causing significant economic losses to farmers, this research addresses agricultural techniques to reduce the monilla (Moniliophthora roreri) in the cultivation of cocoa (Theobroma cacao L.). The implementation of effective management techniques is the key objective to control the disease and increase the sustainability of the crop. The approach applied was a bibliographic study based on technical articles on the control of the monilla, previous studies and scientific articles. Sanitary pruning, integrated pest management, the use of resistant types, biological control with Trichoderma spp., and agroforestry systems were other approaches evaluated. The findings showed that while integrated management allowed production to reach 4.2 quintals per fortnight, sanitary pruning reduced the incidence of diseased fruits by 30%. The resistant versions reduced the initial infection by 40%; biological control increased production by 20%. This study confirmed that the application of these techniques was essential for the control of monilla. These strategies demonstrated a reduction in the disease and managed to improve its yield and reduce damage that affected the crop and, above all, its profitability. Finally, it was recommended that personnel be trained so that they can identify this disease in time and reduce losses. It was also suggested that they carry out a project on genetic improvement in order to be able to use resistant varieties and guarantee their acceptance by farmers.